1988
DOI: 10.1007/bf00133777
|View full text |Cite
|
Sign up to set email alerts
|

The microbial epidemiology of trachoma

Abstract: Detailed longitudinal studies of the microbiology of endemic trachoma in field situations have provided useful information concerning the epidemiology of this blinding disease. This knowledge should be of particular value for the further development of diagnostic techniques, and for the design of future trachoma control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Prouzrokovan je serotipovima A, B, Ba i C Chlamydia trachomatis [2]. Bolest se karakteriše pojavom folikula, papilarne hiperplazije i panusom a u kasnijim stadijumima ožiljcima [3].…”
Section: Uvodunclassified
“…Prouzrokovan je serotipovima A, B, Ba i C Chlamydia trachomatis [2]. Bolest se karakteriše pojavom folikula, papilarne hiperplazije i panusom a u kasnijim stadijumima ožiljcima [3].…”
Section: Uvodunclassified
“…Small studies conducted in Taiwan and Iran in the 1970s and 1980s, which used the micro-immunofluorescence test to type ocular isolates or tear antibody, showed that a single serovar of C. trachomatis usually accounts for all infections in any given household, confirming the importance of transmission within the family. 34,35 Molecular genotyping, usually performed by sequencing the ompA gene after its amplification by a PCR, has enabled us to conduct much larger studies. These investigations have generally confirmed that a single household contains a single genotype, that more than one genotype is present in most if not all trachoma-endemic communities, and that single nucleotide polymorphisms are commonly found in ocular strains.…”
Section: Molecular Toolsmentioning
confidence: 99%